2015
DOI: 10.4103/0973-7847.156340
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical profile of sugarcane and its potential health aspects

Abstract: Sugarcane (Saccharum officinarum Linn.) is an important perennial grass of Poaceae family, indigenous to tropical South Asia and Southeast Asia. It is cultivated worldwide due to the economical and medicinal value of its high yielding products. Sugarcane juice is well known as a raw material for the production of refined sugar and its wax is considered as a potential substitute for the expensive carnauba wax, which is of cosmetic and pharmaceutical interest. Refined sugar is the primary product of sugarcane ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
129
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(139 citation statements)
references
References 29 publications
3
129
0
7
Order By: Relevance
“…La identificación de estos compuestos podría ser útil para tener un control eficiente en el manejo de plagas tales como el barrenador de la caña de azúcar (SAGARPA, 2006) y la mosca pinta (Hernández-Rosas et al, 2010;Alatorre-Rosas y Hernández-Rosas, 2015) siendo estos compuestos atractivos o repelentes de los insectos y en algunos casos, por sus altas concentraciones pueden tener distintos usos, desde farmacéuticos hasta el uso en productos cosméticos (Singh et al, 2015). El objetivo fue, la identificación de compuestos volátiles de las hojas verdes de variedades de caña de azúcar y pastos.…”
Section: Introductionunclassified
“…La identificación de estos compuestos podría ser útil para tener un control eficiente en el manejo de plagas tales como el barrenador de la caña de azúcar (SAGARPA, 2006) y la mosca pinta (Hernández-Rosas et al, 2010;Alatorre-Rosas y Hernández-Rosas, 2015) siendo estos compuestos atractivos o repelentes de los insectos y en algunos casos, por sus altas concentraciones pueden tener distintos usos, desde farmacéuticos hasta el uso en productos cosméticos (Singh et al, 2015). El objetivo fue, la identificación de compuestos volátiles de las hojas verdes de variedades de caña de azúcar y pastos.…”
Section: Introductionunclassified
“…Most of the farmers reported selling sugarcane was a source of livelihood. Reference [15] reported that sugarcane was a major farm enterprise, contributing about 90% to farm income. This is contrary to the study carried out by [16], in which there was a drop in income from sugarcane due to increase in land value.…”
Section: Discussionmentioning
confidence: 99%
“…Sugarcane juice is widely used in India in the treatment of jaundice, hemorrhage, dysuria, anuria, and other urinary diseases. It is considered beneficial for the liver and is recommended that jaundice patients take in a large amount of sugarcane juice for immediate relief [4]. The genetic resources of this plant has been collected, conserved and documented in other parts of the world [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its medicinal value (stemming from the species name officinarum or officinalis which means 'used in medicine') and cultural value were also noted as important traits. It is a valuable medicinal plant, significant in alternative healing methods (Kadam et al, 2008), providing relief against diseases like jaundice, haemorrhage, dysuria, anuria, and other urinary diseases (Singh et al, 2015). Resistance to pest and diseases was the least preferred trait.…”
Section: Farmers' Preferred Sugarcane Traitsmentioning
confidence: 99%